Water-dispersed semiconducting polymer for NIR-II fluorescence imaging and NIR-II laser-triggered photothermal therapy. (February 2023) - Yang, Guangzhao; Wang, Yi; Zhou, Shan; Chen, Lu; Chen, Yang; Liu, Yu; Liang, Xin; Yin, Chao; Zhou, Hui; Fan, Quli
Abstract: Fluorescence imaging in the second near-infrared (NIR-II) window has emerged as a promising imaging method for cancer diagnosis because of its superior properties such as deep penetration depth and high signal to background ratio. The integration of NIR-II imaging and NIR-II photothermal therapy (PTT) has shown great potential in the field of biomedical research and preclinical practice. Semiconducting polymers have several featured advantages, such as easily tunable optical properties, high photostability, and reliable biocompatibility. However, most semiconducting polymer nanoparticles (SPNs) formed using nanoprecipitation method have high accumulation in reticulum endoplasmic system (RES), and their maximum absorption is located in the first near-infrared (NIR-I) window. Therefore, it is required to develop new NIR-II emissive SPNs with the absorption peaks over 1000 nm, which can be triggered by NIR-II light for deep tissue PTT. Herein, we develop an amphiphilic semiconducting polymer (ASP) with the maximum absorption located in the NIR-II window. The amphiphilic feature of ASP drives it to self-assemble into nanoparticles in aqueous media, which show excellent optical properties, low toxicity, and proper size. ASP exhibits not only bright NIR-II fluorescence but also prominent photothermal performance under 1064 nm laser irradiation. Impressively, ASP shows superior accumulation ability in the tumor compared with that in liver or spleen. Taken together, the overall properties of ASP make it a promising NIR-II phototheranostic agent for cancer diagnosis and treatment. Highlights: A novel amphiphilic semiconducting polymer (ASP) is developed. ASP shows superior accumulation ability in the tumor over liver or spleen. ASP is employed for NIR-II fluorescence imaging and NIR-II light-triggered PTT.